NTERNALISASI REVOLUSI MENTAL (Studi Analisis Deskriptif Siswa SMP Plus Ma’arif NU Pangandaran - Hidayat, Yayat (INSPIRASI (Jurnal Kajian dan Penelitian Pendidikan Islam), 2023)
Internalisasi Revolusi Mental…INSPIRASI Vol. 7, No. 2, Juli – Desember 2023 | 91Jurnal Inspirasi – Vol. 7, No. 2, Juli – Desember 2023ISSN 2548-5717INTERNALISASI REVOLUSI MENTAL(Studi Analisis Deskriptif Siswa SMP Plus Ma’arif NUPangandaran)Yayat Hidayat(Program Studi Manajemen Pendidikan IslamSTITNU Al-Farabi Pangandaran)Email: yayathidayat512@yahoo.comABSTRAKFokus penelitian ini yaitu, “Bagaimana Internalisasi Revolusi Mental Siswa SMPPlus NU Ma’arif Pangandaran?”. Jenis penelitian termasuk penelitian kualitatifdeskriptif yaitu kegiatan penelitian yang dilakukan pada objek tertentu secara jelasdan sistematis. Sedangkan metode yang digunakan adalah pendekatan kualitatif.Penelitian ini bertujuan untuk mendeskripsikan Internalisasi Revolusi MentalSiswa SMP Plus NU Ma’arif Pangandaran. Hasil penelitian : 1). Internalisasidiartikan sebagai penghayatan, pendalaman, pengasingan, penggabungan ataupenyatuan sikap, standart tingkah laku, pendapat dan seterusnya di dalamkepribadian. 2). Revolusi Mental adalah transformasi etos, yaitu perubahanmendasar dalam mentalitas, cara berfikir, cara merasa dan cara mempercayai, yangsemuanya menjelma dalam perilaku dan tindakan sehari-hari. Etos ini menyangkutsemua aspek kehidupan, mulai dari ekonomi, politik, sains tekhnologi, seni, agama,dan sebagainya, 3). Internalisasi Revolusi Mental adalah suatu proses secaramendalam tentang nilai-nilai Revolusi Mental yang berjalan di SMP Plus NUMa’arif Pangandaran. Proses internalisasi sangatlah penting dalam RevolusiMental. Oleh karena Revolusi Mental merupakan bagian pendidikan nilai.The focus of this study is, "How is the Internalization of the NU Middle SchoolStudent Mental Revolution Ma'arif Pangandaran?". This type of research includesdescriptive qualitative research, namely research activities carried out on certainobjects clearly and systematically. While the method used is a qualitativeapproach. This study aims to describe the Internalization of the NU Plus MiddleSchool Mental Revolution Ma'arif Pangandaran. Research results: 1).Internalization is defined as appreciation, deepening, exile, combining or unitingattitudes, standard behavior, opinions and so on in the personality. 2). Mental Revolution is a transformation of ethos, which is a fundamental change inmentality, ways of thinking, ways of feeling and ways of trust, all of which aremanifested in everyday behavior and actions. This ethos concerns all aspects oflife, ranging from economics, politics, science to technology, art, religion, etc., 3).The internalization of the Mental Revolution is an in-depth process of the values ofthe Mental Revolution that runs in NU Plus Middle School Ma'arif Pangandaran.The process of internalization is very important in the Mental Revolution. Becausethe Mental Revolution is part of the education of values. The focus of this study is,"How is the Internalization of the NU Middle School Student Mental RevolutionMa'arif Pangandaran?". This type of research includes descriptive qualitativeresearch, namely research activities carried out on certain objects clearly andsystematically. While the method used is a qualitative approach. This study aims todescribe the Internalization of the NU Plus Middle School Mental RevolutionMa'arif Pangandaran. Research results: 1). Internalization is defined asappreciation, deepening, exile, combining or uniting attitudes, standard behavior,opinions and so on in the personality. 2). Mental Revolution is a transformation ofethos, which is a fundamental change in mentality, ways of thinking, ways offeeling and ways of trust, all of which are manifested in everyday behavior andactions. This ethos concerns all aspects of life, ranging from economics, politics,science to technology, art, religion, etc., 3). The internalization of the MentalRevolution is an in-depth process of the values of the Mental Revolution that runsin NU Plus Middle School Ma'arif Pangandaran. The process of internalization isvery important in the Mental Revolution. Because the Mental Revolution is part ofthe education of values.